Malaysia : Staff Report for the 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
The IMF staff report for the 2013 Article IV Consultation focuses on Malaysia's economic developments and policies. The IMF report discusses that continued growth in domestic demand, especially investment, and a pickup in external demand should help maintain robust growth going forward despite the fiscal tightening. Amidst concerns about Malaysia's public finances and sharp narrowing of the external surplus in spring-summer of 2013, authorities have taken timely action to secure fiscal sustainability and assure markets. It suggests that authorities' decisions in 2013 are close to a fiscal policy breakthrough aiming to contain federal debt and related fiscal risks.